Education, labour & science. Perspectives for the 21st century (Frankfurt am Main, 2008)
"This book presents a selection of presentations during the Fifth Congress of the International Network «Regional and Local Development of Work and Labour. The congress took place at the University of Osnabruck in September 2006. However, it was not a traditional congress, but it revived the practice of «future workshops, which were invented by Robert Jungk. The book assembles 33 articles covering all social sciences by authors from 16 different countries: Austria, Brazil, Denmark, Germany, France, India, Italy, Japan, The Netherlands, Nigeria, Norway, Poland, Russia, South Africa, Spain, and Sweden. It is dedicated to the democratization of the different spheres of society from a grassroot-perspective."